Age, gender, and setting's effect on community pharmacists' stress and confidence in the COVID-19 pandemic - Stephanie A. Gernant; Stefanie C. Nigro; Dean G. Cruess; Marie Smith; Nathaniel M. Rickles (Elsevier, 2023)
Background: Reports of increased stress among healthcare workers were commonplace during the early days of the COVID-19 pandemic, but little is known about community pharmacists' experiences. Objective: To characterize community pharmacists' stress and confidence during the early COVID-19 pandemic and identify associated factors. Methods: Pharmacists who worked in a brick-and-mortar community pharmacy (e.g., big-box, chain, independent, or grocery pharmacies) located in Connecticut and had regular face-to-face interaction with the public were surveyed. Survey items were selected from the Perceived Stress Scale-10 (PSS-10) and adapted from the Emergency Risk-Communication (ERC) framework. Data were analyzed using chi-square and ANOVA. Results: Survey results suggested pharmacists experienced moderate levels of stress, as negative responses to PSS-10 items ranged between 6.4% to 43.3%, respectively. Overall, pharmacists had high rates of confidence in their ability to manage the pandemic, agreeing or strongly agreeing that they could manage their own mental health (73.1%), and communicate the risks of the pandemic (72.0%). However, 28.0% reported that they had avoided talking about the pandemic because it made them feel "stressed, or nervous." Women and those working in chain community pharmacies tended to report significantly higher rates of stress to several items in the PSS-10 compared to men and pharmacists working in non-chain settings. Women and chain community pharmacists were also significantly more likely to report overall that they had avoided talking about public health risks because it made them feel anxious, stressed, or depressed (29.4% men vs. 34.5% women χ2 (4) > 22.6, p < 0.01). However, confidence to communicate critical risk messages neither differed between men and women (77.6% men vs. 68.8% women χ2 (4) > 8.3, p = 0.08), nor between chain and non-chain community pharmacists (71.0% chain vs. 73.7% non-chain χ2 (4) > 8.9, p = 0.32). Conclusion: Being female, younger age, and employed at a chain pharmacy were associated with higher rates of stress and lower self-confidence among community pharmacists during the COVID-19 pandemic.